Violência, mídia e juventude: análise sobre o discurso adotado pelo jornalismo impresso sobre a realidade violenta de jovens da periferia da cidade do Natal - Pedrosa, Jasson Matias (2008)
The work that follows has as its main objective the analysis of the discourse of media, with emphasis on newspapers printed on acts and events involving young offenders. The speech adopted by columnists of newspapers, based on formulas and journalistic practices exist, allows the reader a view of what happened in detail. But this wealth of information, contradictorily, it seems not permit, much less to encourage reflection on the what is being read. All information contained in narrative journalism seem to point to the establishment of maintenance of speech reinante of violence and repression against young offenders, from, and generally in the vast majority of cases, from poor neighborhoods and suburbs of large cities. The whole range of such important issues directly related to violence committed by these young people does not appear, does not appear in the text journalism. Words such as "marginal", "square" reinforce prejudices, stigmas against the youth, putting the company on constant alert against such "criminals", "malandros." The result of the survey was partial, but can conclude about the importance of the media against those social phenomena that amedrontam the society at present